Issues Of Clarification Of Problems Of Economic Thought In Eastern And Western Philosophical Teachings - Asrakulova Adiba Nabievna (Periodica Journal, 2024)
This article provides detailed information on the issues of clarification of problems of economic thinking in Eastern and Western philosophical teachings, the positive significance of the spread of Islam in the enrichment of the economic thinking of young people in the acquisition of economic knowledge by the peoples of Central Asia, as well as its economic ideas.
Keywords: spirituality; people; economic thinking